Pengaruh Model Pembelajaran Predict-Observe-Explain Terhadap Hasil Belajar Fisika Siswa Ditinjau Dari Sikap Ilmiah - Viddy Mega Samudera; Joni Rokhmat; Wahyudi Wahyudi (Department of Physics Education, Universitas Mataram, 2017)
This study aims to determine: (1) the influence of Predict-Observe-Explain learning model (X1) toward students' physics learning outcomes (Y); (2) the influence of scientific attitude (X2) toward studentsÃ¢â¬â¢ physics learning outcomes (Y); (3) the effect of interaction between (X1) and (X2) on (Y). This research type is quasi experiment with factorial 2 x 2. Its population is all students of class XI IPA in SMA Negeri 6 Mataram years 2016/2017. Samples were taken using cluster random sampling technique and class XI IPA 4 as experimental class and class XI IPA 3 as control class. Data were taken using multiple choice tests with five alternative answers (learning outcomes) and questionnaires (scientific attitudes). The result data was analyzed using two way analysis of variance (anava) with 5% significant level. The results show that Fcount for influence (X1) = 4.58, (X2) = 25.92, and interaction between (X1) and (X2) is 0.05 with Ftable = 3.97. For the effects of (X1) and (X2) there is Fcount Ã¢â°Â¥ Ftable whereas the interaction effect between (X1) and (X2) is obtained Fcount <Ftabel. Based on the results of this analysis can be concluded that: (1) there is influence of Predict-Observe-Explain learning model toward studentÃ¢â¬â¢s physics learning outcomes; (2) there is influence of scientific attitude toward studentÃ¢â¬â¢s physics learning outcomes; (3) there is no interaction effect between Predict-Observe-Explain learning model with scientific attitude toward student physics learning result.